Lectin histochemistry of intestinal carbohydrate determinants in representatives of different classes of vertebrates. - Antonyuk, R. V.; Lutsyk, A. D. (Морфологія / Morphologia / Morfologìâ, 2015)
Background. Glycoproteins (including mucin) of vertebrate’s intestine play an important role in its protection against chemical and mechanical damage and bacterial attacks. Their diversity was described by many authors, but understanding of their chemical structure remains far from complete. These data can be extended by methods of lectin histochemistry. Objective. To investigate the rearrangement of intestinal carbohydrate determinants in the context of vertebrate evolution. Methods. Distal and proximal segments of small and large intestines of humans (Homo sapiens), laboratory (Wistar) rat (Rattus norvegicus f. Domesticus), rock pigeon (Columba livia), smooth snake (Coronella austriaca), common frog (Rana temporaria), common carp (Cyprinus carpio) that belong to different classes of vertebrates were taken for the experiment. Nine lectins with different carbohydrate specificities: wheat germ (WGA), potato (STA), elderberry bark (SNA), golden rain bark (LABA), locust bark (RPBA), roe carp (CCRA), Phaseolus vulgaris erytroagglutinin (PHA-E), peanut (PNA) and jack fruit (AIA) – were included into the panel. Results. Differences in lectin staining between small and large intestine were more pronounced in higher (human, rat) than in lower (frog, carp) vertebrates. Lectin receptors were more diverse in frog intestine in comparison with carp. Lectin interaction with mucin secretory granules of smooth snake revealed lack of N-acetyl-D-glucosamine residues and abundance of N-acetyl-D-galactosamine determinants. Conclusion. Intestines of all studied vertebrate species demonstrate high content of secretory mucins that exposed terminal acidic carbohydrates including sialic acid. The diversity and differences in the structure of glycans of the digestive tract of vertebrates is apparently determined by several factors – diet, environmental and living conditions, intestinal microbiota interactions etc.